Integrating Geometer’s Sketchpad and Realistic Mathematics Education: A Visual Media Model for Plane Geometry - Redi Hermanto; Satya Santika; Depi Ardian Nugraha; Vepi Apiati (Mosharafa: Jurnal Pendidikan Matematika, 2025)
Permasalahan rendahnya pemahaman mahasiswa terhadap materi geometri bangun datar akibat media pembelajaran yang kurang interaktif dan kontekstual menjadi fokus penelitian ini. Untuk mengatasi hal tersebut, penelitian ini berupaya mengintegrasikan Geometer’s Sketchpad (GSP) dengan pendekatan Realistic Mathematics Education (RME) menjadi sebuah media visual interaktif. Penelitian ini bertujuan menilai kualitas media dari aspek validitas, kepraktisan, dan efektivitas. Proses pengembangan mengikuti model ADDIE, melibatkan 32 mahasiswa pendidikan matematika yang mengikuti perkuliahan geometri di Universitas Siliwangi. Instrumen penelitian menggunakan  lembar penilaian ahli, angket kepraktisan, dan tes penguasaan konsep. Analisis data menunjukkan media telah tervalidasi (87,75%), dinilai praktis (86,5%), dan mampu meningkatkan hasil belajar mahasiswa (N-Gain 0,53). Media ini terbukti layak dan efektif dalam memperkuat pemahaman geometri bangun datar pada mahasiswa. The low level of students' understanding of plane geometry material, attributed to the lack of interactive and contextual learning media, has become the focus of this research. To address this issue, the study aims to integrate Geometer's Sketchpad (GSP) with the Realistic Mathematics Education (RME) approach to develop an interactive visual media. The objective of this research is to evaluate the quality of the media in terms of validity, practicality, and effectiveness. The development process follows the ADDIE model and involves 32 mathematics education students enrolled in geometry courses at Siliwangi University. The research instruments include expert validation sheets, practicality questionnaires, and concept mastery tests. Data analysis indicates that the media has been validated with a score of 87.75%, rated as practical at 86.5%, and demonstrated the ability to improve students' learning outcomes, with a normalized gain (N-Gain) of 0.53. The media is proven to be feasible and effective in enhancing students' understanding of plane geometry.